PENGENALAN JENIS PANTAI DAN ORGANISME PENGHUNI KEPADA SISWA SD NEGERI 78 AMBON - Tubalawony, Simon; Lokollo, Frijona F.; Kalay, Degen E.; Ratuluhain, Eva S.; Wattimena, Marlin C. (Pattimura University, 2025)
Marine environmental damage is one of the problems that has not yet been properly resolved to this day. Dumping waste into the sea is a global issue that the government continues to address by urging the public to preserve the marine environment in order to safeguard nature for the future. This Community Service (PkM) activity is carried out with the aim of fostering a sense of love and care for the marine environment from an early age, so that students are expected to continuously maintain and preserve the marine environment. The PkM activity was held on Wednesday, September 10, 2025, targeting 20 students from grades 1 and 2. The methods carried out in this Community Service Program (PkM) include an initial survey, coordination, preparation of materials, and outreach and implementation. The material was delivered for 60 minutes, followed by a question-and-answer session. During the outreach, the enthusiasm of the students was very high, indicated by the critical questions posed by the students, and the questions asked by the team could be answered well.